Localized learning by emerging multinational enterprises in developed host countries: A fuzzy-set analysis of Chinese foreign direct investment in Australia - Fan, David; Cui, L.; Li, Y.; Zhu, C. (Pergamon, 2016)
Firms learn general international management and foreign market specific knowledge in their internationalization process. Firms’ strategic emphasis on generalized vs. localized learning is an important yet underexplored issue in the extant literature. Drawing on the theoretical framework of dynamic capability, and in the context of emerging multinational enterprises’ FDI into developed host countries, this study examines the equifinal process–position–path configurations of firms that will motivate them to engage in localized learning (as opposed to generalized learning). Utilizing primary and secondary data of eleven Chinese foreign direct investments in Australia, collected at both headquarters and subsidiary levels, we conducted fuzzy-set qualitative comparative analysis (fsQCA) that provided substantial support to our propositions. This study contributes to the internationalization process model by identifying equifinal process–position–path configurations, as well as their core and peripheral conditions that motivate localized learning at both the headquarters and the subsidiary levels.